FUNGSI KERETA API LOKAL DAN KARAKTERISTIK MOBILITAS KOMUTER YOGYAKARTA-SURAKARTA - ABDILLAH, FATHONI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
In travelling, commuters require a decent transportation mode. Train (especially the Yogyakarta to Surakarta municipality commuter lines) is a strategic and dependable mode of transportation due to its advantages. The objectives of this study is to determine the role of the Yogyakarta and Surakarta commuters on the development of the commuter lines, their characteristic and mobility, the problems of the commuter lines, and the ease of access to the station. Mix research method is being utilized in this research with purposive sampling strategy, which is by selecting the sample object that understand and could give sufficient information regarding the research problems. The data collection method is conducted by observation and spreading questionnaire. Those data being obtained in the observation then were tested using descriptive statistic and spatial analysis. The research results is as follows: (1) Prambanan Express and Sriwedari is the most widely used train by the sampled commuters, with proportion 20 and 39 percent respectively, meanwhile for Madiun Jaya Express and Sido Mukti the percentages are 9 and 8 percent respectively